SERUM SODIUM AND SERUM POTASSIUM CHANGES DURING TRANSURETHRAL RESECTION OF PROSTATE GLAND IN PATIENTS UNDER SUBARACHNOID BLOCK - Sunaina N Patel; Nidhi D Patel (National Journal of Medical Research, 2014)
Objective: This prospective study was design to study the changes occurring in serum level of Na & k during TURP in Spinal anaesthesia & also other factor like amount of irrigating fluid absorbed, resection time, height of irrigation, amount of gland resected & concurrent hemodynamic changes occurring during procedure.